Team physician`s corner: Environmental issues for team physicians - DeFranco, M. J.; Baker III, Ch. L.; DaSilva, J. L.; Piasecki, D. P.; Bach Jr., B. R. (The American Journal of Sports Medicine, 2008)
As outdoor sports continue to gain popularity, understanding the environmental factors that may influence athletes is becoming a more important aspect of medical care for team physicians. Temperature, ultraviolet light, lightning, and altitude are some of the most common elements that cause illness. Understanding how to prevent, diagnose, and promptly treat conditions caused by environmental factors is essential to optimizing athletic performance in outdoor sports and avoiding morbidity.